IMPLEMENTASI PERATURAN DAERAH NOMOR 07 TAHUN 2023 TENTANG PENYELENGGARAAN PERUMAHAN DAN KAWASAN PERMUKIMAN STUDI TENTANG PROGRAM BANTUAN RUMAH TIDAK LAYAK HUNI - Saputro, Agil Haryo; Pramono, Joko (Solidaritas, 2024)
Having a livable house is a basic right for the Indonesian people. As stated in the 1945 Constitution, article 28 h resulting from the IV amendment. This research aims to describe the implementation of regional regulation number 07 of 2023 concerning the implementation of housing and residential areas, a study of the assistance program for uninhabitable houses in the city of Surakarta. In this research, the researcher used a qualitative descriptive method using Edward III's theory (1980) with indicators of communication, resources, disposition, bureaucratic structure. The technique for determining informants uses purposive sampling. The method for collecting research data was carried out by means of observation, interviews and documentation. The data analysis used by researchers is Miles and Huberman 2014. The results of the research show that regional regulation number 07 of 2023 concerning the administration of housing and residential areas, the study of the assistance program for uninhabitable houses in the city of Surakarta, can be said to be quite good in terms of the four indicators. However, it is still unfortunate that from the results of interviews in the resource indicators section, facilities were still found to be inadequate. Thus, the government must immediately improve adequate facilities to carry out uninhabitable housing assistance program activities. Because facilities are the main priority in implementing policies so that activities run smoothly.   Keywords: policy implementation, uninhabitable housing assistance program.